2021
DOI: 10.1021/acs.jpcb.1c00540
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Allosteric Territory of Protein Function

Abstract: While the pervasiveness of allostery in proteins is commonly accepted, we further show the generic nature of allosteric mechanisms by analyzing here transmembrane ion-channel viroporin 3a and RNA-dependent RNA polymerase (RdRp) from SARS-CoV-2 along with metabolic enzymes isocitrate dehydrogenase 1 (IDH1) and fumarate hydratase (FH) implicated in cancers. Using the previously developed structure-based statistical mechanical model of allostery (SBSMMA), we share our experience in analyzing the allosteric signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 131 publications
1
16
0
Order By: Relevance
“…An in silico docking report suggested that RIFs, FDX, and other small molecules including a prodrug form of RDV-TP and ivermectin, may bind to SARS-CoV-2 nsp12 [26] at a site that could be involved in allosteric signaling [24]. This hypothetical hotspot lies at the interface between the NiRAN and RdRp domains (Figure 4A), and our results support the existence of allosteric communications between the two nsp12 active sites [23].…”
Section: Antibiotics Targeting Bacterial Rna Polymerase Also Inhibit ...supporting
confidence: 80%
See 4 more Smart Citations
“…An in silico docking report suggested that RIFs, FDX, and other small molecules including a prodrug form of RDV-TP and ivermectin, may bind to SARS-CoV-2 nsp12 [26] at a site that could be involved in allosteric signaling [24]. This hypothetical hotspot lies at the interface between the NiRAN and RdRp domains (Figure 4A), and our results support the existence of allosteric communications between the two nsp12 active sites [23].…”
Section: Antibiotics Targeting Bacterial Rna Polymerase Also Inhibit ...supporting
confidence: 80%
“…For orthosteric ligands that bind to an active site the relevance is clear, but for allosteric ligands the effect cannot be predicted from a simple free energy of binding [82]. The available data argue that SARS-CoV-2 RdRp [23,24,42] and ExoN [83] are subject to allosteric control. Furthermore, while virtual screening is necessary to evaluate millions of compounds as potential novel antivirals, its value for drug repurposing now appears questionable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations